Does the Business Case Matter? The Effect of a Perceived Business Case on Small Firms’ Social Engagement - Panwar, Rajat (Journal of business ethics, 2017)
The business case for social responsibility (BCSR) is one of the most widely studied topics in the business and society literature that focuses on large firms. This attention is understandable because large firms have an obligation to shareholders who, as commonly assumed, seek to maximize returns on their investments, in turn, pressing corporate managers to show that firms’ expenditures in social engagement would pay off. Small firms, on the other hand, rarely face such pressures, yet the BCSR logic is increasingly applied to small firms as well. Our primary objective in this paper is to examine whether and how much do small firm owners’ perceptions of BCSR affect the firm’s social engagement. In finding a fine-grained answer to those questions, we consider BCSR as a two-dimensional construct consisting of tangible and intangible benefits, and also integrate the BCSR perspective with the slack resource perspective to offer a motivation-capacity lens to examine firm’s social engagement. Drawing on a multi-industry sample of 478 small firms in the US, we find that while small firm owners’ perceptions about potential tangible benefits of social engagement are not related to the firm’s social engagement, perceptions about potential intangible are positively related. Firm's financial performance is also positively related to its social engagement, but there is no interaction between potential benefits and financial performance. This study contributes to an improved understanding about small firms’ social engagement, which still remains an understudied area. Our results are in line with studies which argue that firms’ social engagement is a response to institutional factors.